Analisis Hubungan Kekuatan Otot Lengan terhadap Kecepatan Renang Gaya Bebas 50 Meter - Ashari Efendi; Nopri Abadi Miko (Jurnal Sporta Saintika, 2025)
This study aimed to determine the relationship between arm muscle ability and 50-meter freestyle swimming speed among students of the Physical Education Study Program at Universitas Muhammadiyah Mahakarya Aceh. The study employed a quantitative approach with a correlational research design. The population consisted of students enrolled in the swimming course, while the sample comprised 20 students selected using purposive sampling based on predetermined criteria. Arm muscle ability was measured using a 60-second push-up test, whereas freestyle swimming speed was assessed through a 50-meter freestyle swimming test with time recorded in seconds. Data were analyzed using descriptive statistics, normality tests, linearity tests, and Pearson Product-Moment correlation analysis at a significance level of 0.05. The descriptive analysis showed that the mean score of arm muscle ability was 38.65 repetitions (SD = 7.24), while the mean 50-meter freestyle swimming time was 35.72 seconds (SD = 3.41). The results of the Pearson correlation test revealed a correlation coefficient of r = -0.785 with a significance value of p = 0.000 (p < 0.05). These findings indicate a significant and strong negative relationship between arm muscle ability and 50-meter freestyle swimming speed. Students with better arm muscle ability tended to achieve shorter swimming times, indicating higher swimming speed. It can be concluded that arm muscle ability is an important factor associated with 50-meter freestyle swimming performance among Physical Education students.